Multiple Photon High Vibrational CH Overtone Resonant and One-Photon Dissociation of Toluene Radical Cation. Issue 5 (1985) - Simonov, A. P.; Abakumov, G. A.; Yaroslavtzev, V. T.; Lunchev, V. A.; Fedorov, E. A.
Abstract : Photodissociation of molecular radical cations of toluenes C7 H 8 +· (I), C6 H5 CD 3 +· (II), C7 D 8 +· (III), cycloheptatriene C7 H 8 +· (IV), and benzene has been studied by the method of two-pulse two-colour laser photolysis of molecules in a mass spectrometer using wavelengths 1064, 532, and 355 nm. The I ions formed due to sequential two-photon ionization of toluene molecules by the 266 nm radiation isomerize supposingly into 5-methylene-cyclohexadiene (VI). Two- and three-photon stepwise dissociation of the I and II isomers (VI and VI-d3, respectively) induced by the 1064 nm radiation has a resonance at the third overtone level of CH aliphatic bond stretching vibrations. Internal energy randomization in the two-photon dissociation is much less for VI-d3 as compared to VI. The mechanisms of isoenergetic dissociation (two- and one-photon processes induced by the 1064 and 532 nm radiations, respectively) are different: the one-photon decay via an electronically excited state proceeds considerably faster than the two-photon decomposition does in the ground state. The photodissociation cross sections have been determined. It has been shown that the intensity of CH stretching vibration overtones can be essentially higher for radical cations than for the neutral molecules.